Characterisation and optimisation of mechanical, physical and thermal properties of short abaca (musa textile nee) fibre reinforced high impact polystyrene composites - Hadi, Agung Efriyo (2011)
Mechanical properties of polymer composites are influenced by many factors such as the types of fibres, the types of polymer matrix, the additives used and the adhesion between fibres and polymer matrix. To improve the interfacial adhesion between high impact polystyrene (HIPS) matrix and abaca fibres, the study of optimum use of coupling agent maleic anhydride (MAH) and impact modifier, styrene-butadienestyrene, (SBS) is presented in this research. Abaca fibre reinforced high impact polystyrene (HIPS) composites are produced with different fibre loadings (30, 40 and 50 wt%), different compositions of coupling agent, MAH (1,2 and 3 wt%) and different compositions of impact modifier (4,5 and 6 wt%). A response surface methodology using Box-Behnken design (BBD) is used in the design of experiments and analysis of results. Statistical analysis of mechanical properties gives very satisfactory model accuracy, because the coefficient of determinant is 0.9817 for impact strength, 0.9789 for tensile strength, 0.9672 for tensile modulus, 0.9700 for flexural strength, and 0.9747 for flexural modulus. In this study, loading abaca fibre 36.76 wt%, maleic anhydride 3 wt% and impact modifier 4 wt% are parameters that are optimum for individual impact strength. On the other hand, optimum individual tensile strength and tensile modulus were achieved when the loading of abaca fibre is close to 40.76 wt%, maleic anhydride 3 wt% and impact modifier 6 wt%, but the optimum individual flexural strength and flexural modulus were found when loading of abaca fibre is close to 40.03 wt%, maleic anhydride 3 wt% and impact modifier 4 wt%. Based on the analysis of variance (ANOVA) and BBD analysis, the Brinell hardness number (BHN) was not influenced by the significant increase of abaca fibre and coupling agent (maleic anhydride (MAH)) and also by the interaction between impact modifier and coupling agent (maleic anhydride (MAH)). The interaction between abaca fibre and impact modifier, represented by the negative coefficient X13 (β₁₃ = -0.1413 and p-value < 0.05) indicated unfavourable effect and partitioning influence in the abaca fibre reinforced HIPS composites. The interaction between abaca fibres and impact modifier is less likely for Brinell hardness number (BHN) of the composites. The physical properties by natural fibre had a great importance especially in the structure of natural fibre which reinforced matrix. Based on response surface methodology, Box-Behnken design, the individual optimum conditions of melt flow index was found with loading of abaca fibre 36.71 wt%, maleic anhydride 3 wt% and impact modifier 4.02 wt%. The optimum condition for water absorption of abaca fibre reinforced HIPS composites followed the decreasing trend of value of melt flow index. Differential scanning calorimetry (DSC) was used to study the thermal behaviour of abaca fibre reinforced high impact polystyrene (HIPS) composites. In this research, glass transitions temperature (Tg) of neat HIPS occurred below the Tg of optimum condition of composites as the temperature of an amorphous state. The endothermic peak of composites was in the range of 430 0C – 435 0C including neat HIPS and it was observed that enthalpy of abaca fibre reinforced HIPS composites was yielded below the enthalpy of neat HIPS of 748.79 J/g. In this research, thermogravimetric analysis (TGA) within optimum condition of abaca fibre reinforced HIPS composites was compared to the neat HIPS. The measurements were carried out in temperatures ranging from 25 0C – 600 0C at heating rate of 20 0C min-1 and nitrogen gas flow of 50 mL min-1. The results from TGA analysis have shown that the combination of the coupling agent maleic anhydride, impact modifier and abaca fibre has improved the thermal stability of composites.